(untitled) (Applied Biological Research, 2023)
A study was conducted at the Stress Physiology Laboratory, AAU, Jorhat, Assam (India) during kharif season 2016-2017. Rice genotypes (146 nos.) collected from different ecotypes were screened for anaerobic tolerance based on their survivality. Of the genotypes evaluated, six genotypes viz., ‘Ronga Lahi’, ‘Ronga Bao’, ‘Bangali Lahi’, ‘Suwag Moni Horu’, ‘Asra 123’ and ‘Asra 8’ were selected as anoxia tolerant genotypes on the basis of seed germination, seedling survival and growth. These genotypes were also evaluated for amylase activity. The result revealed a significant variation in genotypes during anoxic germination in terms amylase activity. Higher α- and β-amylase activities were observed in ‘Asra 123’, followed by ‘Asra 8’ as compared to the susceptible genotype ‘IR-64’. Increased amylases activity in tolerant genotypes might be attributed to the production and maintenance of sufficient amount of soluble sugar under anoxic condition during germination. The study revealed that ‘Asra 123’, ‘Asra 8’, ‘Ronga Lahi’, ‘Ronga Bao’, ‘Bangali Lahi’ and ‘Suwag Moni Horu’ could successfully be germinated and established under anoxic condition.